11 -- 2.x = x -- ( 25 -- 9 )
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 11 - ( 15 + 11 ) = x - ( 25 - 9 )
11-15-11=x-25+9
-15=x-16
x=1
b, 2 - x = 17 - ( - 5 )
2-x=22
x=-20
c, x - 12 = ( - 9 ) - 15
x-12=-24
x=-12
d, 9 - 25 = ( 7 - x ) - ( 25 + 7 )
(7-x)-32=-16
7-x=16
x=-9
#H
a) \(\dfrac{7}{9}\times\dfrac{13}{25}\times\dfrac{9}{7}=\left(\dfrac{7}{9}\times\dfrac{9}{7}\right)\times\dfrac{13}{25}=1\times\dfrac{13}{25}=\dfrac{13}{25}\)
b) \(\dfrac{5}{9}\times\dfrac{21}{25}+\dfrac{21}{25}\times\dfrac{4}{9}\)
\(=\dfrac{21}{25}\times\left(\dfrac{5}{9}+\dfrac{4}{9}\right)\)
\(=\dfrac{21}{25}\times1=\dfrac{21}{25}\)
c) \(\dfrac{19}{5}\times\dfrac{11}{16}-\dfrac{9}{5}\times\dfrac{11}{16}\)
\(=\dfrac{11}{16}\times\left(\dfrac{19}{5}-\dfrac{9}{5}\right)\)
\(=\dfrac{11}{16}\times2=\dfrac{22}{16}=\dfrac{11}{8}\)
\(11-\left(15+11-2.x\right)=x-\left(25-9\right)\)
\(11-15-11+2x=x-16\)
\(2x-x=-16-11+15+11\)
\(1x=-1\)
\(x=-1\)
a)2-x=17-(-5)
2-x=17+5
2-x=22
x=2-20
x=-20
b)x-12=-9-15
x-12=-24
x=(-24)+12
x=-12
c)11-(15+11)=x-(25-9)
11-26=x-16
-15=x-16
x=-15+16
x=1
d)x-25=(7-x)-(25+7)
x-25=(7-x)-32
2x-25=7-32
2x-25=-25
2x=(-25)+25
2x=0
x=0:2
x=0
tick cho mk nha bạn
a)2-x=17-(-5)
2-x=17+5
2-x=22
x=2-20
x=-20
b)x-12=-9-15
x-12=-24
x=(-24)+12
x=-12
c)11-(15+11)=x-(25-9)
11-26=x-16
-15=x-16
x=-15+16
x=1
d)x-25=(7-x)-(25+7)
x-25=(7-x)-32
2x-25=7-32
2x-25=-25
2x=(-25)+25
2x=0
x=0:2
x=0
\(a,2-x=17-\left(-5\right)\)
\(\Rightarrow2-x=17+5\)
\(\Rightarrow2-x=22\)
\(\Rightarrow x=2-22\)
\(\Rightarrow x=-20\)
Vay...
\(b,11-\left(15+11\right)=x-\left(25-9\right)\)
\(\Rightarrow11-26=x-16\)
\(\Rightarrow-15=x-16\)
\(\Rightarrow-15+16=x\)
\(\Rightarrow x=1\)
11-2x=x-25+9
11-2x=x-16
-2x-x= -16-11
-3x= -27
x= -27:(-3)
x=9